An Automated BIM Model to Conceptually Design, Analyze, Simulate, and Assess Sustainable Building Projects. (6th November 2014) - Jalaei, Farzad; Jrade, Ahmad
Abstract : Quantifying the environmental impacts and simulating the energy consumption of building's components at the conceptual design stage are very helpful for designers needing to make decisions related to the selection of the best design alternative that would lead to a more energy efficient building. Building Information Modeling (BIM) offers designers the ability to assess different design alternatives at the conceptual stage of the project so that energy and life cycle assessment (LCA) strategies and systems are attained. This paper proposes an automated model that links BIM, LCA, energy analysis, and lighting simulation tools with green building certification systems. The implementation is within developing plug-ins on BIM tool capable of measuring the environmental impacts (EI) and embodied energy of building components. Using this method, designers will be provided with a new way to visualize and to identify the potential gain or loss of energy for the building as a whole and for each of its associated components. Furthermore, designers will be able to detect and evaluate the sustainability of the proposed buildings based on Leadership in Energy and Environmental Design (LEED) rating system. An actual building project will be used to illustrate the workability of the proposed methodology.